2015
DOI: 10.7763/ijiet.2015.v5.618
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of SPSS Course to Students Attitudes toward Statistics and Achievement in Statistics

Abstract: The data analysis will be calculated using the Wilcoxon test and t test. The results of the data processing show that here is a significant increase in the cognitive aspects of learning Statistics after using SPSS but there is a significant decrease in achievement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 0 publications
3
22
0
Order By: Relevance
“…Perhaps the level of students' anxiety towards statistics was higher at the beginning of the course and decreased during their participation in the course. Similar experiences have been reported by Jatnika (2015). To confirm this assumption further research should be undertaken.…”
Section: Descriptive Statisticssupporting
confidence: 75%
See 2 more Smart Citations
“…Perhaps the level of students' anxiety towards statistics was higher at the beginning of the course and decreased during their participation in the course. Similar experiences have been reported by Jatnika (2015). To confirm this assumption further research should be undertaken.…”
Section: Descriptive Statisticssupporting
confidence: 75%
“…One of these is Zapletal and Pacakova (2013), who highlighted the usage of statistical software to motivate students to study statistics. Furthermore, Jatnika (2015) has studied the effect of an SPSS course on students' attitudes towards statistics and achievement in statistics. The author tried to determine whether there was a significant difference in students' attitudes before and after participating in an SPSS course.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Attitudes toward statistics itself have not been studied as the influential factor in SPSS acceptance models in the past, moreover, it may be expected that students' attitudes toward statistic change after attending statistics and the SPSS course (Jatnika, 2015). Some studies also found out, that there are only a small proportion of students who believe that statistic will be useful and important in their chosen career, even after the implementation of additional organized trainings (Hagen et al, 2013).…”
Section: Perceived Usefulness Of Statisticsmentioning
confidence: 94%
“…Yet SPSS is popular for apply in statistical analysis in social science papers and it is also accepted by the researchers in different areas such as government, healthcare, education, etc. (Jatnika, 2015). Meanwhile, AMOS is an adding to SPSS software, which is particularly used for Structural Equation Modeling, path analysis, and confirmatory factor analysis.…”
Section: Fdi Enterprisesmentioning
confidence: 99%